2012
DOI: 10.1128/aem.00150-12
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response of the Cellobiose Dehydrogenase Gene to Cello- and Xylooligosaccharides in the Basidiomycete Phanerochaete chrysosporium

Abstract: Cellobiose dehydrogenase (CDH) gene transcripts were quantified by reverse transcription-PCR (RT-PCR) in cultures ofPhanerochaete chrysosporium supplemented with various cello-and xylooligosaccharides in order to elucidate the mechanism of enhanced CDH production in xylan/cellulose culture. Cellotriose and cellotetraose induced cdh expression, while xylobiose and xylotriose induced expression of cellobiohydrolase genes, especially cel7C. The basidiomycete Phanerochaete chrysosporium produces various extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Taking into account the order of different endoglucanases secreted by microbes growing on various carbon resources , it could be concluded that the oligosaccharide profiles under different growth conditions should be dynamic, and some enzyme components, such as An EglA, could be hydrolyzed to produce a series of oligosaccharides that would induce additional components of GHs . Because water‐insoluble substrates cannot be transported into the cell, cellulolytic microbes require a fine‐response mechanism to regulate the secretion of additional cellulases .…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the order of different endoglucanases secreted by microbes growing on various carbon resources , it could be concluded that the oligosaccharide profiles under different growth conditions should be dynamic, and some enzyme components, such as An EglA, could be hydrolyzed to produce a series of oligosaccharides that would induce additional components of GHs . Because water‐insoluble substrates cannot be transported into the cell, cellulolytic microbes require a fine‐response mechanism to regulate the secretion of additional cellulases .…”
Section: Discussionmentioning
confidence: 99%
“…When the white-rot P. chrysosporium is grown on spruce wood, expression of genes encoding ligninolytic enzymes (MOX and GLOX) is upregulated, whereas cellulase genes are expressed in a more constitutive manner (209). Earlier reports have shown that CDH expression is also induced early, particularly by products of cellulase action (280). In a recent comprehensive study, Miyauchi et al used an integrative omics approach to show that the saprophytic white-rot fungus Pycnoporus coccineus simultaneously secretes GHs, esterases, and oxidoreductases when grown on various lignocellulosic substrates (148).…”
Section: Enzyme Production During Lignocellulose Depolymerizationmentioning
confidence: 99%
“…To date, the literature reports the characterization of about 30 CDHs from their native fungal producers. The formation of CDH in vitro requires the presence of insoluble cellulose or soluble cello-oligosaccharides, which act as an 148 Daniel Kracher, Roland Ludwi g inducer (Hori et al, 2012). CDH is secreted into the extracellular space and typically represents about 0.5-2.5% of the total secreted protein on a mass basis (Zámocký et al, 2006).…”
Section: Diversity and Classification Of Cellobiose Dehydrogenases 4mentioning
confidence: 99%